(untitled) (Global Journal of Management and Business Research, 2020)
Industry 4.0, known as industry revolution 4.0, is going to be a business environment in which the labor market will get replaced by machines that can think like humans. Value chains of companies will get interconnected with data. Robots with artificial intelligence will be performing operations that were previously done by humans. Further, those will achieve more accuracy and efficiency in such activities. With this revolution, companies require to focus more on strategic human resource management, as human capital is going to be a much more valuable asset in industry 4.0 where organizations will be able to create sustainable competitive advantage through human capital. Artificial intelligence (AI) is going to be the fuel in industry 4.0. AI based machines will represent the majority of the labor force. This paper is to introduce AISHRM conceptual model which stands for the use of #x201C;Artificial Intelligence based Strategic Human Resource Management for industry 4.0#x201D;. This conceptual model developed based on the strategic human resource management theory of #x201C;resource-based view of a firm#x201D; or #x201C;resource advantage theory#x201D;.